Extracurricular activities associated with stress and burnout in preclinical medical students - Jawad Fares; Zein Saadeddin; Hayat Al Tabosh; Hussam Aridi; Christopher El Mouhayyar; Mohamad Karim Koleilat; Monique Chaaya; Khalil El Asmar (Springer, 2019)
This study aims to assess the prevalence of stress and burnout among preclinical medical students in a private university in Beirut, Lebanon, and evaluate the association between extracurricular involvement and stress and burnout relief in preclinical medical students. A cross-sectional survey was conducted on a random sample of 165 preclinical medical students. Distress level was measured using the 12-item General Health Questionnaire (GHQ-12) while that of burnout was measured through the Maslach Burnout Inventory-Student Survey (MBI-SS). The MBI-SS assesses three interrelated dimensions: emotional exhaustion, cynicism, and academic efficacy. Extracurricular activities were divided into four categories: physical exercise, music, reading, and social activities. All selected participants responded. A substantial proportion of preclinical medical students suffered from stress (62%) and burnout (75%). Bivariate and multivariate regression analyses revealed that being a female or a 1st year medical student correlated with higher stress and burnout. Music-related activities were correlated with lower burnout. Social activities or living with parents were associated with lower academic efficacy. The high stress and burnout levels call for action. Addressing the studying conditions and attending to the psychological wellbeing of preclinical medical students are recommendations made in the study.